Development of dispersive XAFS system for analysis of time‐resolved spatial distribution of electrode reaction. (16th July 2015) - Katayama, Misaki; Miyahara, Ryota; Watanabe, Toshiki; Yamagishi, Hirona; Yamashita, Shohei; Kizaki, Terue; Sugawara, Yoshimi; Inada, Yasuhiro
<x xml:space="preserve">Abstract</x> Apparatus for a technique based on the dispersive optics of X‐ray absorption fine structure (XAFS) has been developed at beamline BL‐5 of the Synchrotron Radiation Center of Ritsumeikan University. The vertical axis of the cross section of the synchrotron light is used to disperse the X‐ray energy using a cylindrical polychromator and the horizontal axis is used for the spatially resolved analysis with a pixel array detector. The vertically dispersive XAFS (VDXAFS) instrument was designed to analyze the dynamic changeover of the inhomogeneous electrode reaction of secondary batteries. The line‐shaped X‐ray beam is transmitted through the electrode sample, and then the dispersed transmitted X‐rays are detected by a two‐dimensional detector. An array of XAFS spectra in the linear footprint of the transmitted X‐ray on the sample is obtained with the time resolution of the repetition frequency of the detector. Sequential measurements of the space‐resolved XAFS data are possible with the VDXAFS instrument. The time and spatial resolutions of the VDXAFS instrument depend on the flux density of the available X‐ray beam and the size of the light source, and they were estimated as 1 s and 100 µm, respectively. The electrode reaction of the LiFePO4 lithium ion battery was analyzed during the constant current charging process and during the charging process after potential jumping.